Charter of the City of Schenectady 97 (1869) - (:unkn) unknown (My University, 1863)
An Ordinance Prohibiting the Obstructing of Side-Walks, and for Other Purposes, § 3: It shall not be lawful for any person to discharge any gun, pistol or other fire-arms, except in a shooting gallery, within the lamp district of this city; and every person offending in this respect shall be punished by fine not exceeding ten dollars and the costs of the suit, and to stand committed until such fine and costs be paid, not exceeding ten days.
Keywords: DISCHARGE